Acute myocarditis or the kounis syndrome: Role of cardiac MRI and speckle-tracking echocardiography in diagnosis - Karaca, Oğuz; Çakal, Beytullah; Çakal, Sinem Deniz; Türkmen, Muhsin (My University, 2014)
Introduction: The Kounis syndrome and acute myocarditis are two distinct clinical entities, which could share nearly the same symptomatology as well as ECG (electrocardiography) and laboratory findings. Case Presentation: First case was a 39-year-old male presented with acute chest pain and inferolateral ST elevation on ECG. The second case was a 29-year-old male presented with chest pain and diffuses ST elevation. Diagnosis of acute myocarditis was achieved by demonstrating subepicardial contrast enhancement as well as atypical involvement in both of our clinical cases. Conclusions: We reported two cases in which specific imaging modalities (cardiac magnetic resonance imaging and speckle-tracking echocardiography) were used when the signs and symptoms were indistinguishable.
Keywords: Kounis Syndrome; Myocarditis; Magnetic Resonance Imaging; Speckle-Tracking Echocardiography